Contraceptive methods and the transmission of HIV: implications for family planning. Issue 2 (April 1994) - Daly, C C; Helling-Giese, G E; Mati, J K; Hunter, D J
Abstract : Heterosexual transmission is the predominant mode of spread of the Human Immunodeficiency Virus (HIV) in most of the world. Whether the use of hormonal contraceptives, IUDs and spermicides is associated with an increased or decreased risk for HIV acquisition remains controversial. Several mechanisms whereby contraceptive methods may influence the transmission of HIV have been proposed. As contraceptive use increases among women of reproductive age, the group most vulnerable to HIV infection, any associations between contraceptive method and HIV risk become even more important. The available studies of these associations are predominantly cross-sectional and give conflicting results. We review the published evidence for associations between HIV and individual contraceptive methods. At this time no definitive conclusions regarding these associations can be drawn. Further research, especially prospective epidemiological studies and basic biological research on mechanisms of heterosexual transmission and the effect of contraceptives on these mechanisms, is urgently needed.